2018
DOI: 10.1155/2018/7080673
|View full text |Cite
|
Sign up to set email alerts
|

A Novel AMR-WB Speech Steganography Based on Diameter-Neighbor Codebook Partition

Abstract: Steganography is a means of covert communication without revealing the occurrence and the real purpose of communication. The adaptive multirate wideband (AMR-WB) is a widely adapted format in mobile handsets and is also the recommended speech codec for VoLTE. In this paper, a novel AMR-WB speech steganography is proposed based on diameter-neighbor codebook partition algorithm. Different embedding capacity may be achieved by adjusting the iterative parameters during codebook division. The experimental results p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…For each encoder, there is a maximum PESQ score. This standard gives an assessment of speech quality from −0.5 to 4.5, yet the result is frequently confined to the range [1.0, 4.5], similar to a mean opinion score (MOS) scale from 1 (worst) to 5 (best) [16,27,17]. In such a scale, the PESQ score equal to 2 is selected as the intelligibility threshold.…”
Section: Speech Quality Assessment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each encoder, there is a maximum PESQ score. This standard gives an assessment of speech quality from −0.5 to 4.5, yet the result is frequently confined to the range [1.0, 4.5], similar to a mean opinion score (MOS) scale from 1 (worst) to 5 (best) [16,27,17]. In such a scale, the PESQ score equal to 2 is selected as the intelligibility threshold.…”
Section: Speech Quality Assessment Methodsmentioning
confidence: 99%
“…Better concealment schemes and statistical security than the existing AMR FCB steganographic schemes. [16] Is based on the algorithm of diameterneighbour codebook partition that provides the AMR-WB coder with flexibility in steganographic capacity with various iterative parameters.…”
Section: Scheme Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the two steganographic SBS methods carried out by balanced and unbalanced VQ codebook partitioning can generate stego-speech signals with similar quality to cover speech signals. In [6], an AMR-WB speech steganography system was proposed based on diameter-neighbor codebook partition method. It was shown that speech steganographic system can provide higher and flexible embedding capacity without noticeable decrease in speech quality and better performance against statistical steganalysis.…”
Section: Introductionmentioning
confidence: 99%